(untitled) (LEARNing Landscapes, 2023)
Design thinking is emerging as a popular student-centric teaching approach in Nepal. However, limited research has been done to understand how teachers feel about using these approaches in their classrooms. In-depth interviews with five design-thinking teachers revealed that cultural context plays a crucial role when new teaching approaches are used. The pedagogical and mindset shift required by teachers when exploring new teaching approaches directly affects their emotions, resulting in varying levels of joy or frustration. Critical reflection helps teachers manage their emotions, which is crucial in navigating challenges and emotional exhaustion.